2022
DOI: 10.1055/a-1778-4529
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Care in Specialist Ophthalmology Departments: Structure and Impact of the COVID-19 Pandemic

Abstract: Background: Specialist ophthalmology departments contribute to the surgical care of German patients. Outpatient and inpatient surgeries were restricted during the COVID-19 pandemic and led to a sharp decline in the number of cases in ophthalmological care. The aim of this analysis was to improve the understanding of the logistic structures of medical facilities as well as the effects of the pandemic. Material/method: Based on reported process data, a sample of the specialist ophthalmological departme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…This observation concurs with a German study which reported that most ophthalmic procedures, especially cataract surgery, continued to decline even after stabilization of the provided health-care services following the pandemic. 17 Following the worldwide pandemic lockdown, there has been a significant backlog of operable cataract surgeries, 12 , 18 and this backlog is expected to increase. However, the number of health-care staff and operating room availability can vary based on staff being affected by COVID which will inhibit timely clearance of this backlog.…”
Section: Discussionmentioning
confidence: 99%
“…This observation concurs with a German study which reported that most ophthalmic procedures, especially cataract surgery, continued to decline even after stabilization of the provided health-care services following the pandemic. 17 Following the worldwide pandemic lockdown, there has been a significant backlog of operable cataract surgeries, 12 , 18 and this backlog is expected to increase. However, the number of health-care staff and operating room availability can vary based on staff being affected by COVID which will inhibit timely clearance of this backlog.…”
Section: Discussionmentioning
confidence: 99%